Toward the Controlled Synthesis of Highly Dispersed Metal Clusters Enabled by Downsizing Crystalline Porous Organic Cage Supports. Issue 8 (16th June 2022) - Zhu, Liying; Zhang, Suyun; Yang, Xin‐Chun; Zhuang, Qiang; Sun, Jian‐Ke
Abstract: The controlled synthesis of subnanometer‐sized metal clusters (MCs) presents a fascinating prospect for the research of size‐dependent properties. In this study, a facile approach by employing porous racemic organic cage crystals as supports for immobilizing a broad range of noble MCs (e.g., Ru, Ir, Rh) is reported. Downsizing the support to the nanoscale leads to resultant MCs with precisely controlled sizes < 0.7 nm. Such enhanced stabilization ability is a result of enhanced metal–support interactions as well as the nanoconfinement of organic cages in controlling the growth of MCs. Moreover, the obtained MCs display excellent catalytic performance in a series of liquid‐phase reactions owing to a decrease in the diffusion resistance from the substrate to MCs immobilized by the nano‐sized cage support. Abstract : Downsizing the racemic organic cage supports leads to stabilize a number of well‐dispersed, long‐term stable metal clusters of sub‐nano size (<0.7 nm) with high catalytic performance. This success relies on the enhanced binding power of nanosized cage supports to metal species, owing to the increased surface area over volume and the nanoconfinement from the intrinsic pores of organic cages.